Pendugaan laju respirasi pisang barangan menggunakan model arrhenius - Arief Fazlul Rahman; Muhammad Faisal (Universitas Muhammadiyah Mataram, 2023)
The respiration process cannot be separated from horticultural products after harvest. So we need a method to determine the rate of respiration (CO2 production), one of which is the Arrhenius model. The purpose of this study was to predict the CO2 production rate of Barangan bananas using the Arrhenius model. CO2 production of Barangan bananas with different harvesting ages (10 and 11) weeks was measured using the Continuous Gas Analyzer IRA-107 Shimadzu where the banana samples were placed in a respiration chamber, refrigerator for low temperature storage. The measured respiration rate data was then estimated using the Arrhenius model. When the storage temperature increases, the rate of CO2 production will increase. At the harvest age of 11 and 10 weeks the higher the storage temperature, the CO2 production rate will increase. The relationship between CO2 production rate and storage temperature can be solved using the Arrhenius model. The results of the prediction of the Arrhenius model found a coefficient of determination of 0.91-0.94. The k values of 10 weeks of harvest (0.1, 0.24, 0.36) and k of 11 weeks of harvest (0.19, 0.31, 0.49) were calculated using the equation obtained using the Arrhenius model. Value of Ea harvested 33.76 kJ/mol at 10 weeks and 45.83 kJ/mol at 11 weeks. The respiration rate produced at 10 and 11 weeks was different, where the CO2 production rate at 11 weeks at harvest was 77.98 ml/kg.hour with predicted results of 75.76 mm/kg.hour and at 10 weeks at harvest 65.80 ml/kg.hour with a predicted result of 68.21 ml/kg.hour. The results of the Arheniuss model can be used to estimate the CO2 production rate of Barangan bananas during storage